2017
DOI: 10.2471/blt.16.172924
|View full text |Cite
|
Sign up to set email alerts
|

Equity trends in ownership of insecticide-treated nets in 19 sub-Saharan African countries

Abstract: ObjectiveTo examine the change in equity of insecticide-treated net (ITN) ownership among 19 malaria-endemic countries in sub-Saharan Africa before and after the launch of the Cover The Bed Net Gap initiative.MethodsTo assess change in equity in ownership of at least one ITN by households from different wealth quintiles, we used data from Demographic and Health Surveys and Malaria Indicator Surveys. We assigned surveys conducted before the launch (2003–2008) as baseline surveys and surveys conducted between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…A recent study on equity trends in ownership of ITNs involving eight West African countries (including Benin, Burkina Faso, Mali, Nigeria, Senegal etc.) and 11 other sub-Saharan African countries, showed that richer households were more likely to own ITNs than the poorest households [ 45 ]. The relatively lower percentage of ITNs possession by the population of the poorest quintile has been attributed to their inability to afford the cost of the ITNs and probably as a result of low access to health care among the poorest populations [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on equity trends in ownership of ITNs involving eight West African countries (including Benin, Burkina Faso, Mali, Nigeria, Senegal etc.) and 11 other sub-Saharan African countries, showed that richer households were more likely to own ITNs than the poorest households [ 45 ]. The relatively lower percentage of ITNs possession by the population of the poorest quintile has been attributed to their inability to afford the cost of the ITNs and probably as a result of low access to health care among the poorest populations [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…These poor households and communities are not identified in national surveys for targeted interventions. Evidence for improving household ownership of ITN through mass distribution campaigns has yielded mixed results in sub-Saharan Africa; in some countries, equity between the relatively wealthier and the less wealthy has increased, while in others, it decreased [ 30 32 ]. Deliberately addressing inequity and specifically developing strategies aimed at improving community socio-economic status may improve malaria control for poor communities [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several multi-country analyses included ITN use among children under the age of five into a composite index for maternal and child health to track country and regional progress toward the Millennium Development Goals [ 22 ]; these studies found that, although relative inequalities have generally been narrowing, appreciable differences between the poorest and the least poor persist. There have been a number of evaluations that focused on a single malaria intervention (most commonly ITNs) [ 23 , 24 ]. To the best of our knowledge, only one earlier study [ 5 ] has assessed equity across a range of malaria interventions in a large number of endemic African countries.…”
Section: Introductionmentioning
confidence: 99%